Examination of The Doping Knowledge Levels of Natural Sled Athletes in Terms of Some Variables - Erol Baykan; Mehmet İnan; Ufuk Apur; Ünsal Sevindik; Fatih Akgul (Selcuk University, 2023)
This study was conducted to measure the doping knowledge levels of athletes in the natural sled discipline actively working in Turkey. In this context, a personal information form developed by the researcher and the "Attitude Scale Towards Doping Use" developed by Şapçı (12) were administered to 55 athletes who participated in the 2020 Natural Sled Turkey Championship. The collected data were initially entered into the SPSS 26 statistical program. Descriptive statistics, independent samples t-test, and one-way analysis of variance (ANOVA) were used for data analysis. Additionally, the Mann Whitney U test was used for the scores of the international medal variable. In one-way analysis of variance, the Scheffe Post Hoc multiple comparison test was used to determine which groups had significant differences. As a result of the statistics conducted, it was concluded that male athletes participating in the research had higher doping knowledge levels than female athletes, and the knowledge levels of athletes who were not subjected to doping tests were lower than those of athletes who were subjected to doping tests.